An Analysis of the Phenomenon of Adapting Online Literature into Chinese Web Short Dramas - Xiamiao, Liang; Qiong, Wu (Business Administration and Management Journal Review, 2025)
Online literature, as a key medium for cultural transmission, has also flourished and gradually become a significant source of creative inspiration for web short drama production. This study selected 30 web short dramas from the trending lists of the three major platforms—iQIYI, Youku and Tencent Video—resulting in a total of 90 web short dramas as research samples. Employing sample analysis and literature review approaches, the study examines the phenomenon of adapting online literature into Chinese web short dramas and proposes corresponding strategies. The findings reveal three main issues with these adaptations: first, the serious repetition and homogenization of genres; second, the "formulaic" nature of the content; and third, the poor artistic quality of the adaptations, which can mislead public values. It reflects the issues of limited innovation in adapted works, a lack of cultural depth, and the potential negative impact on the audience’s aesthetics and values. The study suggests breaking free from genre constraints, exploring content diversification, emphasizing positive value output, improving adaptation quality, and advancing the healthy progress of both Chinese web short dramas and online literature.